Language Teachers' Strategies for Enhancing Vocabulary Mastery: A Retrospective Study Using Blooket - Fahmi, Sahal; Purnawan, Ari (Universitas Muhammadiyah Yogyakarta, 2000)
Background: Foreign language instruction in Indonesia remains teacher-centered with minimal technology use. Digital tools like Blooket now offer educators opportunities to boost student engagement and vocabulary acquisition through gamification. Objective: This study examines the impact of language teachers in improving students' vocabulary mastery through Blooket. Methods: A retrospective qualitative approach was employed, focusing on 15 language teachers at SMA Negeri 1 Imogiri. The research highlights the effectiveness of gamification strategies in vocabulary instruction. The researcher employed a case study methodology, utilizing qualitative research techniques and questionnaire design for this study. In this study, 15 participants, who were language teachers with a minimum of five years of teaching experience in English and German at SMA Negeri 1 Imogiri, were specifically asked questions about vocabulary instruction. Findings: Findings indicate that a combination of gamified learning and varied teaching methods significantly enhances students' vocabulary acquisition. Students will acquire new words more successfully if the teacher integrates interactive and contextualized learning experiences, such as game-based learning, real-world applications, and multimodal instruction. Conclusion: This study contributes to the existing literature by emphasizing the role of teachers in integrating gamification to foster vocabulary mastery.